Cessation of cytokinesis in Schizosaccharomyces pombe during growth after release from high hydrostatic pressure treatment - Arai, S.(Nihon Univ., Fujisawa, Kanagawa (Japan). Coll. of Bioresource Sciences); Kawarai, T; Arai, R; Yoshida, M; Furukawa, S; Ogihara, H; Yamasaki, M (Bioscience, biotechnology, and biochemistry, 2008)
On the basis of our previous study concerning the effect of high hydrostatic pressure treatment (HPT) on Escherichia coli FtsZ ring (bacterial cytoskeleton) formation, we aimed to determine the effect of HPT on the growth properties of a representative eukaryotic microbe, Schizosaccharomyces pombe, in relation to the behavior of genuine cytoskeletons. Microtubules were visualized with GFP-linked alpha-tubulin. Actin-related cytoskeletons were fluorescently stained with rhodamine-phalloidin. We observed growth retardation of about 10h in post growth after HPT (75 MPa, 30 min, 28 deg C), which caused only a little loss of viable cells. In accordance with the period of growth retardation, cessation of cytokinesis and disappearance of the contractile ring (composed of actin, myosin II, and other proteins), directly participates in cytokinesis, continued for 18 h after HPT. On the other hand, the microtubules disappeared only for 6 h after HPT. Based on these observations, the contractile ring was the site most sensitive to HPT resulting in the cessation of cytokinesis.